ASUPAN ENERGI TERHADAP STATUS GIZI ANAK TK AN NAMIROH PUSAT PEKANBARU - Annisa Zabaldi; Riska Epina Hayu; Eva Mayasari (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
The status of good nutritional on children is the determiner of success in growth phase of children. Preschool children really need food nutrition to fulfill their nutritional needs. The status of good nutritional on children is influenced by some factors, one of them is energy consumption. This study was to determine the correlation between energy consumption and nutritional status of preschool children at the main of TK An Namiroh using cross sectional design, there were 154 children who selected by simple random sampling. Data on children's nutritional status were conducted by anthropometric assessment using scales and microtoise, then calculated by Z-score using the U BMI index, while the total of energy consumption on children used semi-quantitative food frequency questionnaire. This type of study is quantitative. The subjects of this study as main informants were parents of TK An Namiroh’s students. The processing and data analysis using computerization with chi-square test with significant level of 95. The findings of this study indicate that there are 57.9% of children with normal energy consumption as thin category in nutritional status, 60.9% of children with normal energy consumption as normal category in nutritional status, 71.4% of children with normal energy consumption as fat category in nutritional status, 42.1% of children with non-normal energy consumption as thin category nutritional status, 39.1% of children with abnormal energy consumption as normal category in nutritional status, and 28.6% of children with abnormal energy consumption as fat category in nutritional status. Based on the conducted tests, it shows that no significant correlation between energy consumption and nutritional status at the main of TK An Namiroh children in Pekanbaru.